Current approaches to treatment of pain in the low part of back - N. G. Voropai; O. B. Doronina (Бюллетень сибирской медицины)
We described the modern point of view in the pathogenesis of the acute and chronicle low back pain, conception of the tree components formation of the chronicle pain: nociceptive, neuropathic and psychogenetic. Whereby, it was offered the ways of the pathogenetic treatment. We described and substantiated the modern way of treatment of the back pain. We generalized the results of our own experience of using Nurophen for treatment of the acute phase of the back pain in the low part of the back. We showed the efficiency of the Nurophen for treatment of the acute pain in the low part of the back and prevention of the formation of the chronicle pain syndrome.